Evaluasi Penggunaan Teknologi Potpres Organik terhadap Keberhasilan Penanaman Puspa, Salam, dan Gayam di Demplot Restorasi Merapi Pasca Erupsi 2010 - , ESTU BAMBANG SETYONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi eruption that occurred in October 2010 have led to the death and destruction of existing vegetation, around 3000 hectares of national park area experienced serious impacts. Beside the vegetation damage, around 150 million m 3 eruption materials covered the land national parks with varying thickness. Post-eruption restoration have been done in order to restore forest conditions both habitat and biodiversity. One of the activities carried out by the construction of restoration demonstration plots. Planting was done by applying technology of organic potpress to overcome the constraints thickness of volcanic ash. This study aims to determine the growth of puspa, salam, and gayam plantation, the effect of using organic potpress technology and the interaction between species with treatment given. This research was carried out using Incompletely Block Design so the sample unit for each species can be different. Measurements were conducted on three species of plants such as puspa, salam and gayam with plant spacing used was 4 x 5 m. The variables measured were survival percentage, plant height and stem diameter. The analysis of T-test of data was using Microsoft Excel program, to determine the effect of using of organic potpres on growth of plant and interaction between species. The result showed that the survival percentage of all species was 57,97%. Salam has superior growth because its adaptability is fairly high to the survival of 67,85%, the added average height to the treatment without organic potpres was 6,51 cm, 0,24 cm added diameter, while the added average treatment organic potpres 4,34 cm and average diameter of 0,25 cm. Puspa had a survival rate of 60,23%, with an added average height at treatment without organic potpres 8,60 cm with an average diameter of 0,23 cm, while the treatment potpres 4,28 cm added in height and the average diameter 0,24 cm. Survival rates of gayam 45,83% with the added average height on treatment without organic potpres 6,31 cm and diameter 0,23 cm, average added height with potpres 4,16 cm and average diameter 0,25 cm. Plants without organic potpress treatment having a better high growth, mean while plants that use organic potpress has a better diameter growth. Organic potpres treatment was given significant to added height to the three species but not significant to added diameter, therefore it is necessary to do further study.